Leveled Managerial Training of Central Java Cooperative and Micro, Small and Medium Enterprises (MSMEs) Training Center: Key to Success of Central Java MSMEs Upgrading - Fatoni, Mahfud Heru (Yayasan Adra Karima Hubbi, 2024)
In recent decades, the role of Micro, Small, and Medium Enterprises (MSMEs) in supporting the national economy has been increasingly recognized. The purpose of this study is to evaluate the impact of the tiered managerial training program of the Central Java Cooperative & MSMEs Training Center on the managerial capabilities of MSMEs and how this program contributes to increasing the scale of their businesses. In addition, this study also aims to provide recommendations for strategies to improve the effectiveness of similar training in the future in order to optimally encourage MSMEs towards a larger and more competitive business scale. The research method used in this study is descriptive qualitative, the data used in this study were collected through various techniques, including observation, in-depth interviews, and document analysis. The results of the study showed a positive impact of the training. an increase in the average turnover of participants, which reached 224%, an increase in participant assets by 168%, an increase in the number of workers recruited by training participants reaching 209%. Through strategies that include strengthening the global market-oriented curriculum, more sustainable mentoring, integration of digital technology, strengthening alumni networks, focusing on product innovation, cooperation with financing institutions, and data-based evaluation, the effectiveness of this training can be further improved.